INTERAKSI FAKTOR KENDALI TEKTONIK, PERMUKAAN LAUT DAN PERUBAHAN KLIM DI DAERAH TELUK KLABAT, KABUPATEN BANGKA INDUK, BANGKA - S. Hidayat; Herman Moechtar (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The study of the Quarternary deposits in Klabat gulf areas was based on the analyses of the sedimentology and stratigraphy of fifteen borehole information obtained along west to east. The penetration of the bore head varied from 3.50 to 16.80 m from + 21 m to - 4 m of sea-level. Whereas, the Quarternary sediments in the studied area can be divided into seven sedimentary environments, consisting of alluvial fan (FKa), swamp (FRw), floodbasin (FCb), deltaic (FDt), sand beach (FPp), nearshore (FLdp), and nearshore to offshore (FLdp to FLlp) deposits. Based on the lateral and vertical sedimentary environment correlations, the Quaternary stratigraphic succession can be divided into four sedimentary intervals (IP I to IV). Each interval is typically for topography and elevation changes which is controlled by changes of the sedimentary environment systems. The controlling main factor of the sedimentary environment system changes was regional and local tectonics. Changes in tectonic regime are important upon a tidal flat sedimentation.Â Keywords: facies, paleoenvironment, tectonic